2013
DOI: 10.1177/1098612x13487360
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Coxiella burnetii infection in a breeding cattery at the centre of a Q fever outbreak

Abstract: The potential role of cats in transmitting Coxiella burnetii to humans was highlighted in a Q fever outbreak, linked to a caesarean section in a breeding queen, in an Australian small animal veterinary hospital. The objectives of this study were to evaluate the C burnetii seroreactivity of the breeding queen and other cats residing at the same breeding cattery (n = 27) and to evaluate C burnetii infection of the breeding queen by molecular and histological methods. Three assays [complement fixation test (CFT),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 40 publications
0
52
0
Order By: Relevance
“…Moreover, no molecular techniques were employed to verify the Coxiella species observed by Cooper et al (2011) or Shapiro et al (2016). Similarly in a Sydney veterinary clinic in 2010, where a number of clinical staff contracted a C. burnetii infection following caesarean of a breeding cat (Kopecny et al, 2013), despite positive serological tests from the cat in question and clinical staff to C. burnetii, parturient material did not show any histological evidence of sepsis and molecular analyses of C. burnetii failed to amplify the diagnostic targeted gene, IS1111.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, no molecular techniques were employed to verify the Coxiella species observed by Cooper et al (2011) or Shapiro et al (2016). Similarly in a Sydney veterinary clinic in 2010, where a number of clinical staff contracted a C. burnetii infection following caesarean of a breeding cat (Kopecny et al, 2013), despite positive serological tests from the cat in question and clinical staff to C. burnetii, parturient material did not show any histological evidence of sepsis and molecular analyses of C. burnetii failed to amplify the diagnostic targeted gene, IS1111.…”
Section: Discussionmentioning
confidence: 99%
“…Q fever is considered to occur worldwide, except in New Zealand (Greenslade et al, 2003). Traditionally considered an occupational risk for abattoir workers and farmers, exposure to C. burnetii can be acquired through contact with, and inhalation of, infected tissues from domestic ruminants and companion animals (Maurin and Raoult, 1999;Kopecny et al, 2013). Diagnosis is usually undertaken through serological testing with clinical presentations of Q fever ranging from acute to chronic and can include post-Q fever fatigue syndrome; asymptomatic Q fever represents over 54-60% of infections (Maurin and Raoult, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of research in Australia tends to focus on analysis of notified cases (35), unusual outbreaks, (36, 37), or animal and environmental sources (38). However, a recent study by Bond et al (39) demonstrated the application and outcomes of taking a One Health approach to an outbreak associated with a goat farm.…”
Section: Resultsmentioning
confidence: 99%
“…6 Antibodies against C. burnetii have been detected in the serum of cats worldwide. 7 Moreover, it has been hypothesized that cats have been responsible for transmission of C. burnetii to humans in Q fever outbreaks due to exposure to parturient queens, in which various degrees of seroprevalence have been detected. 7À10 Nagaoka et al 11 provided the first evidence of active infection, isolating 9 of 29 cases of C. burnetii from vaginal swabs of domestic queens, and C. burnetii DNA was amplified through PCR assay from 3 out of 37 uterine tissues from cats with and without a history of reproductive abnormalities.…”
Section: Introductionmentioning
confidence: 99%